UMKM CERDAS HUKUM SYARIAH (Edukasi Pelaku Usaha Mikro Pasar Tradisional di Desa Ngrogung Kecamatan Ngebel Tahun 2025) - Nurhalizah Nurhalizah; Khoirul Fathoni (Social Science Academic, 2025)
This study aims to analyze the role of Micro, Small, and Medium Enterprises (MSMEs) in East Java in sustaining and supporting the regional economy during the Covid-19 pandemic. MSMEs are considered a vital sector in strengthening the national economy due to their significant contribution to job creation, gross domestic product (GDP), and economic resilience at the community level during crises. The research employs a descriptive qualitative method using secondary data obtained from previous studies, official publications, online news, and reports from relevant institutions such as Bank of Indonesia, the Central Statistics Agency (BPS), and the Ministry of Cooperatives and MSMEs. The analysis focuses on examining the development of MSMEs in East Java during the pandemic, the challenges they faced, and the adaptation strategies undertaken by business actors. The findings reveal that although the Covid-19 pandemic caused serious impacts such as declining demand, distribution disruptions, and financing constraints, MSMEs in East Java continued to make a substantial contribution to the regional economy. Data from the East Java Office of Cooperatives and MSMEs recorded that MSMEs contributed 57.52% to East Java’s GRDP, with an increase of approximately 414,000 new MSME units each year. Moreover, MSMEs in specific sectors, such as food and online trade, demonstrated relative resilience by adapting through digitalization and the use of e-commerce platforms. These findings indicate that MSMEs not only serve as an economic buffer during crises but also act as a driving force for economic recovery in the post-pandemic period.